Leveraging the semantics of topic maps : Second International Conference on Topic Maps Research and Applications, TMRA 2006, Leipzig, Germany, October 11-12, 2006 : revised selected papers - TMRA; Maicher, Lutz; Sigel, Alexander; Garshol, Marius (Lecture Notes in Computer Science, 2007)
The papers in this volume were presented at TMRA 2006, the International Conference on Topic Maps Research and Applications, held October 11-12, 2006, in Leipzig, Germany. TMRA 2006 was the second conference of an annual series of international conferences dedicated to Topic Maps in research and industry. Topic maps are continuously gaining more and more attention in science and ind- try; they are "crossing the chasm." The TMRA series provides a platform for resear- ers in the topic maps community to meet for exciting exchanges in a stimulating setting. The uniqueness of TMRA is its focus on both sides of the same coin: scientific research on topic maps and upcoming applications in industry. In the autumn of 2005 the first TMRA conference took place in Leipzig. The p- ceedings have been published in this LNAI series as volume 3873. It was amazing to see how ideas and solutions from TMRA 2005 matured within the last year to full products or projects. The overall success of TMRA 2005 encouraged us to improve this conference series for the topic maps community: More people were attracted, and the scientific quality was enhanced. The TMRA 2006 program attracted a very international crowd of about 80 att- dees, hosted in the completely new media campus of the Leipzig Media Foundation.